'Travelling landscapes' and the potential of Artscapes. (October 2022) - Stiassny, Noga
What does it mean to represent trauma, heritage and/or terror-related landscapes in the present day? This article aims to offer a new perspective on the ability of such representations to initiate a journey by means of artistic creation; the author refers to such artworks as ' Artscapes ', claiming that Artscapes make feasible a seemingly contradictory act: on one hand, 'time travel' that assists in commemorating the past(s), and on the other, 'space travel' that has the ability to challenge collective memories, narratives and even myths associated with that past(s). By focusing on a growing trend towards diasporic Artscapes within Israeli art as a test case of this genre, the article explores the potential possessed by such works to negotiate 'diasporic memories' within Zionism's national ethos.